Program Layanan Navigator untuk Meningkatkan Kepuasan Pasien Kanker - Jelita, Jelita; Allenidekania, Allenidekania; Nuraini, Tuti; Gayatri, Dewi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
The cancer patient navigator service program is designed to help patients access the information and services needed during the cancer patient's treatment journey towards satisfaction. The purpose of this study was to determine the effectiveness of the cancer patient navigator service program to improve patient satisfaction in cancer care. This study was a literature review conducted using the systematic review method. The authors used several research article databases, namely ProQuest, ScienceDirect, SpringerLink, AscoPub without limiting the year of publication of the article. The article selection process refers to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. There were 7 articles that were reviewed and met the criteria. The article was a study using the randomized controlled trial method and is criticized using a special instrument, namely the Critical Appraisal Skills Program. Based on the results of the review, several determinants of cancer patient satisfaction are the quality of health services, communication with service providers, and social and emotional support. The cancer patient navigator service program contributes positively to patient satisfaction in optimizing support for cancer patients during the treatment journey. Furthermore, it was concluded that the navigator service program is successful in improving cancer patient satisfaction.Keywords: cancer patients; patient navigator; satisfaction ABSTRAK Program layanan navigator pasien kanker dirancang untuk membantu pasien mengakses informasi dan layanan yang diperlukan selama perjalanan pengobatan pasien kanker terhadap kepuasan. Tujuan studi ini adalah untuk mengetahui efektivitas program layanan navigator pasien kanker untuk meningkatkan kepuasan pasien dalam perawatan kanker. Studi ini merupakan tinjauan literatur yang dilakukan dengan metode systematic review. Penulis menggunakan beberapa basis data artikel penelitian yaitu ProQuest, ScienceDirect, SpringerLink, AscoPub tanpa membatasi tahun penerbitan artikel. Proses pemilihan artikel dilakukan mengacu kepada Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ada sejumlah 7 artikel yang ditelaah dan memenuhi kriteria. Artikel merupakan penelitian dengan metode randomized controlled trial dan dikritik menggunakan instrumen khusus yaitu Critical Appraisal Skills Programme. Berdasarkan hasil review, beberapa faktor penentu kepuasan pasien kanker adalah kualitas layanan kesehatan, komunikasi dengan penyedia layanan serta dukungan sosial dan emosional. Program layanan navigator pasien kanker berkontribusi positif terhadap kepuasan pasien dalam mengoptimalkan dukungan bagi pasien kanker selama perjalanan perawatan. Selanjutnya disimpulkan bahwa program layanan navigator untuk berhasil meningkatkan kepuasan pasien kanker.Kata kunci: pasien kanker; navigator pasien; kepuasan